Lithosphere Protection with Hardening Phosphate-Containing Soil-Cement Technology - Svatovskaya, Larisa; SychovÐ°, Anastasia; Sychov, Maxim (International Journal of Engineering and Technology, 2018)
This research is relevant in the light of a need to protect lithosphere from pollution. A solution to this problem can be the exercise of a geoecoprotective function by using building and construction technologies. Phosphate-containing bonding agents usually have low solubility in water. They are made of aluminosilicates that occur in common clay. These minerals react with phosphoric acid to release phosphates and silica gel with absorption properties. The purpose of this research is to make fake rocks from phosphate clay material, intended for building and construction purposes, and to investigate their longevity. The material used was treated to neutralize and detoxify the mobile ionic contaminants and heavy metal compounds, as well as petroleum pollutants, so that at the end we could get construction material like fake rocks or improved aggregates that would be good for the environment. These cement systems are called the geoecoprotective systems. The leading methods that were applied were thermodynamic and experimental studies of service and geoecoprotective properties of phosphate-containing cement systems, more specifically fake landscape rocks. Selected studies lasted for more than 10 years, and were carried out in accordance with the guidelines, adopted in the Russian Federation. This research shows that phosphate-containing cement systems made from contaminated clay/sandy artificial soils have long-lasting properties like strength, frost resistance, water resistance and contaminant binding. From this perspective, they are good for building and construction. For example, they can be used to improve the contaminated soil on road construction sites by detoxifying it until water-resistant products, and to make long-lasting water-resistant solutions from local raw materials that would be good for waste storage. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â